Gram-Scale Synthesis and Optical Properties of Self-Trapped-Exciton-Emitting Two-Dimensional Tin Halide Perovskites - Yifeng Xing; Jialin Yin; Yifei Qiao; Jie Zhao; Haiyang He; Danyang Zhao; Wanlu Zhang; Shiliang Mei; Ruiqian Guo (Nanomaterials)
Lead halide perovskites (LHPs) have superior luminescent properties, but their toxicity hinders their commercialization, arousing interests in tin halide perovskites as environmentally friendly substitutes for LHPs. Herein, we synthesized a series of two-dimensional tin halide perovskite ODASnBr4-xIx (ODA denotes 1,8-octanediammonium, X = 0, 1, 2, 3, 4) microcrystals via an aqueous-phase method. The differences between ODASnI4 and ODASnBr4 in luminescent properties and morphological characteristics were systematically discussed for the first time and attributed to light-driven ligand-to-metal charge transfer. The prepared ODASnBr4 has a PL peak at 567 nm and a PL QY of 99%, and the white light-emitting diodes fabricated with ODASnBr4 and commercial blue phosphors realized a luminous efficacy of up to 96.27 lm/W, which demonstrated the remarkable potential of ODASnBr4 microcrystals for high-efficiency white light-emitting diode applications.